Vanillin Attenuates Proinflammatory Factors in a tMCAO Mouse Model via Inhibition of TLR4/NF-kB Signaling Pathway. (21st May 2022) - Wang, Ping; Li, Chunyi; Liao, Guolei; Huang, Yihuan; Lv, Xuxian; Liu, Xudong; Chen, Wenli; Zhang, Lei
Highlights: Vanillin reduces brain infarct volume and promoted motor function in tMCAO mice. Vanillin reduces the expression of IL-1β and TNF-α in tMCAO brain and vitro microglia. Vanillin inhibits activation of microglia by inhibiting TLR4/NF-κB signal pathway. Abstract: Vanillin has been reported to reduce hippocampal neuronal death in rat models of global cerebral ischemia. However, the immunoregulatory mechanism of vanillin in ischemic stroke is still unclear. To investigate the role of vanillin in a mouse model of ischemic stroke, we administered vanillin to mice after transient middle cerebral artery occlusion (tMCAO) by tail vein injection. Vanillin reduced infarct volume and improved motor function in mice after ischemia and reperfusion. IL-1β and TNF-α were decreased in ischemic brain tissue of tMCAO mice after vanillin treatment compared with saline treatment. Similar effects were observed using the in vitro LPS-stimulated microglia cell model. Moreover, the reduced expression of proinflammatory cytokines in the vanillin group was related to TLR4/NF-κB signaling. Taken together, the findings suggest that vanillin decreased microglial activation by inhibiting the TLR4 /NF-κB signaling pathway, which reduced expression of proinflammatory cytokines IL-1β and TNF-α, and finally reduced the infarct volume and improved motor function in tMCAO mice.